Revitalizing The Ideological Values Of Pancasila As Antithesis Of Religious Radicalism Community Service In Karangduren Village Kebonarum Of Klaten - Suryo Ediyono (Pancaran Pendidikan, 2017)
The ideology of radical-terrorism is an interesting remark to be understood by the Karangduren Klaten village community as an effort in preventing the entry value that is against the ideology of Pancasila. The supreme divinity value of Pancasila ideology one in the reform era has been challenged by the wave of globalization on information. Socialization on the divinity values aims to stimulate public awareness on the threat of radical ideology of terrorism that potentially grow and develop in the village of Karangduren, Kebonarum, Klaten. This study covers the fields of nationalism and identity with the preaching method and focus of discussion. The Ideology of divinity axiologically and epistemologically comprising of divinity, humanity, unity, democratic and justice values which need to be delivered through specific form of communication which can be adjusted to community’s life in the village of Karangduren. Language as a tool in which various information can be accessed by people living in both rural and urban transition strongly influenced by factors of traditional cultural practices that are still upheld in dealing with modernity. The current actual discourse of terrorism needs to be understood and useful as countering radicalism through familiarization the noble values exemplifications as deeply held by the community leaders and the local youth movement ‘Karang taruna; through the use of appropriate language on the context of Karang duren citizens.